Sistem Pakar Psikologi Perkembangan Anak Menggunakan Algoritma Cosine - Pelsri Ramadar Noor Saputra (Sekolah Tinggi Ilmu Komputer PGRI Banyuwangi, 2023)
An expert system is a system that is used to find a solution to an existing problem by using the knowledge base that is stored in the system. Expert systems are not used to replace existing experts, but rather aim to help the work of experts. With this system, ordinary people can solve certain problems from simple to complex without the need for experts in that field. As for experts, this system can be used as an experienced assistant. The expert application that is being developed in this task aims to detect the psychology of child development based on the symptoms that are observed. This application uses the Cosine Algorithm as a calculation formulation. All symptoms will be displayed, and those selected will be automatically processed using the cosine algorithm to obtain disease results. When the symptoms are selected again, the data will be recalculated from the beginning based on the selected symptoms. Based on the results of the trials that have been conducted, it has been shown that while the calculation using the cosine algorithm is somewhat complex, the accuracy of the cosine calculation is high in determining the child's psychological condition based on the selected symptoms.